2020
DOI: 10.1016/j.engstruct.2019.110120
|View full text |Cite
|
Sign up to set email alerts
|

Fragility functions for a reinforced concrete structure subjected to earthquake and tsunami in sequence

Abstract: Many coastal regions lying on subduction zones are likely to experience the catastrophic effects of cascading earthquake and tsunami observed in recent events, e.g., 2011 Tohoku Earthquake and Tsunami. The influence of earthquake on the response of the structure to tsunami is difficult to quantify through damage observations from past events, since they only provide information on the combined effects of both perils. Hence, the use of analytical methodologies is fundamental. This paper investigates the respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…As suggested by Petrone et al, (2020) due to the fundamentally different structural responses to both perils, the direct economic losses of the aggregated building portfolios for six scenario earthquakes and the corresponding tsunamis have been separately estimated. Hence, all effects related to cumulative damage have been disregarded.…”
Section: Results: Scenario-based Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested by Petrone et al, (2020) due to the fundamentally different structural responses to both perils, the direct economic losses of the aggregated building portfolios for six scenario earthquakes and the corresponding tsunamis have been separately estimated. Hence, all effects related to cumulative damage have been disregarded.…”
Section: Results: Scenario-based Risk Assessmentmentioning
confidence: 99%
“…2.1. This decision is based on the recent findings of Petrone et al, (2020) who found 215 fundamentally different structural responses to both perils. As a consequence, the authors argued that the intensity of the seismic ground motion does not play a significant role in the building's structural tsunami response unless it induces structural yield.…”
Section: Scenario-based Risk Assessmentmentioning
confidence: 99%
“…Several empirical fragility functions for the assessment of buildings (Koshimura et al, 2009;Mas et al, 2012;Suppasri et al, 2014;Charvet et al, 2015;Chock et al, 2016) and infrastructure (Eguchi et al, 2014;Hatayama, 2014) have been derived from observed damage in the 2004 Indian Ocean, 2009 Samoa, 2010 Chile, and 2011 Tohoku tsunamis. Recently, analytical fragility functions were derived from numerical simulations of building response under tsunami inundation (Petrone et al, 2017;Alam et al, 2018;Karafagka et al, 2018;Páez-Ramírez et al, 2020), and under sequential earthquake and tsunami impact (Park et al, 2012;Attary et al, 2019;Petrone et al, 2020). Only a few studies exist that move from fragility to vulnerability modeling .…”
Section: Gaps In Physical Vulnerabilitymentioning
confidence: 99%
“…An important gap related to risk assessment for tsunamis (and in general) is the lack of a streamlined and standard workflow for modeling the multi-hazard and multi-risk aspects. Currently, most studies consider the different hazards to be independent or "simultaneous" (e.g., earthquake and tsunami as independent events); whereas, few works consider interacting hazards such as coupled simulation of tsunami and earthquake (De Risi and Goda, 2016;Goda et al, 2017;Goda and De Risi, 2018;Ordaz et al, 2019;Park et al, 2019), the cumulation of tsunami and earthquake damages and losses (Ordaz, 2015;Attary et al, 2019;Park et al, 2019;Petrone et al, 2020), and interaction of tsunami and aging infrastructure (Akiyama et al, 2020).…”
Section: Assessing Tsunami Risk In a Multi-hazard And Multi-risk Framework (R5)mentioning
confidence: 99%
“…Recent developments in the design of tsunami-resistant onshore structures have heightened the need to improve the capacity of building structures including strength, stiffness and ductility to overcome earthquakes and tsunamis sequentially (Rossetto et al 2019;Petrone et al 2020) and also to reduce the hydrodynamic impact forces exerted on the surface of structures. It has been observed that elevated structures and the presence of break-away walls and openings could be effective strategies to reduce wave-induced pressures (Thusyanthan and Madabhushi 2008;Wilson et al 2009;Lukkunaprasit et al 2009;FEMA 2011;Triatmadja and Nurhasanah 2012;Chinnarasri et al 2013;Hartana and Murakami 2015;Ghosh et al 2016;Park et al 2017;Tomiczek et al 2019).…”
Section: Introductionmentioning
confidence: 99%